A novel recombinant BCG-expressing pro-apoptotic protein BAX enhances Th1 protective immune responses in mice. Issue 2 (August 2015) - Li, Guanghua; Liu, Guoyuan; Song, Na; Kong, Cong; Huang, Qi; Su, Haibo; Bi, Aixiao; Luo, Liulin; Zhu, Lin; Xu, Ying; Wang, Honghai
Highlights rBCG::BAX induces macrophage apoptosis in vitro and in vivo. rBCG::BAX facilitates mycobacterial antigen presentation. rBCG::BAX enhances Th1 protective immune responses in mice.